Disiplin Belajar dan Lingkungan Sekolah Serta Dampaknya terhadap Peningkatan Hasil Belajar Siswa Kelas X MPLB SMKN 3 Bandung - Imaniyati, Nani; Sepdian, Sepdian (Universitas Pendidikan Indonesia (UPI), 2024)
The purpose of this research is to analyze the influence of learning discipline and school environment to learning achievement of X MPLB Student in SMKN 3 Bandung. The research method used in this research is explanatory survey with the questionnaire distributed to the amount of 130 students which are analyzed with descriptive and inferential technique. The result showed by multiple regression regression, the learning discipline and school environment significantly influence the learning achievement of student with the value of influence 73,7% simultaneously.